Investigation of arsenate phytotoxicity in cucumber plants - Czech, Viktória (Acta Biologica Szegediensis, 2008)
Arsenate is reduced to As(III) and causes the formation of free radicals in plants. Arsenic induces oxidative stress in the cell wall region and destroys the membrane permeability. Therefore the effect of arsenate on ion efflux, H2O2 concentration, ascorbate concentration, ascorbate oxidase (AAO) activity and malondialdehyde formation was investigated in cucumber. The cucumber seedlings have a very sensitive period during their development. Under As(V) treatment of 7-day-old plants the roots, hypocotyls and leaves are flaccid and the fresh weight of the roots decreases because of the efflux of water and solutes. H2O2 significantly decreases while ascorbic acid concentration does not change compared to the control roots. In the hypocotyls H2O2 does not change but ascorbic acid significantly increases. Ascorbic acid oxidase activity is higher in the roots and smaller in the hypocotyls. As(V) significantly lowers AAO activity in the roots (about 50%) but increases in hypocotyls of 5-day-old plants. Ascorbic acid protects the plants by preventing lipid peroxidation so the hypocotyls remains turgid, and the inhibition of growth is much smaller.